The Effect of Shelf Life and the Effectiveness of Biopesticide Fobio in Controlling Stem Rot Disease in Vanilla Plants (Vanilla planifolia Andrews) - Mutiara Alyzza Bilqis; Sri Wiyatiningsih; Tri Mujoko (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2026)
Stem rot disease caused by Fusarium oxysporum poses a significant challenge to vanilla (Vanilla planifoliaAndrews) cultivation. The use of microbial-based biopesticides, such as FOBIO, provides an environmentallyfriendly alternative to reduce reliance on chemical fungicides. This study aimed to evaluate the effects of FOBIObiopesticide storage age and concentration on disease intensity and vanilla plant growth (Vanilla planifoliaAndrews). The research was conducted from March to June 2025 in Dusun Tukum using a factorial completelyrandomized design with two factors: FOBIO storage age (6 months and 1 year) and concentrations (5, 7.5, and 10mL/L of water), with three replications totaling 105 plants. Data were analyzed using Analysis of Covariance(ANCOVA), followed by the Least Significant Difference (LSD) test at a 5% significance level. The resultsdemonstrated that the FOBIO application significantly reduced disease intensity compared to the control (p <0.05). The most effective treatment was FOBIO stored for 1 year at a concentration of 7.5 mL/L of water (FP23B),resulting in a final disease intensity of 6.365 compared to 38.255 in the control. FOBIO also increased leaf numberand stimulated plant growth during the vegetative phase, including accelerating flower development. The FOBIObiopesticide is an environmentally friendly alternative for controlling stem rot in vanilla and serves as a biologicalcontrol agent with potential to support sustainable agriculture.